Cypria lacrima sp. nov. a new ostracoda (candonidae, crustacea) species from Texas, U.S.A. - (:unkn) unknown (Academia Sinica, 2017)
A new ostracod species, Cypria lacrima sp. nov. (Cyclocypridinae) is proposed from an artesian well in Hays County, Texas, U.S.A. The species differs from its conspecies with the following characteristics: unique shape and pit ornamentation on carapace, absence of “e” and “g” setae on both walking and cleaning legs, long gamma seta on Mandibular palp, asymmetric clasping organs and differences in the shape and size of other cheatotaxial parts. A detailed comparison among the species of the genus is provided along with ecological implications. This is a new report of the species from an artesian well which increases geographic distribution of the genus in the southern parts of the US. © 2017 Academia Sinica. all rights reserved.
Keywords: Artesian well; Cyclocypridinae; Hays County; New species; Taxonomy